2011
DOI: 10.1021/jp206258u
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Hydrogen and Nitrogen Gases with Porous Graphene Membrane

Abstract: We designed a series of porous graphene as the separation membrane of H 2 /N 2 . The selectivity and permeability could be controlled by drilling various nanopores with different shapes and sizes. The mechanisms of hydrogen and nitrogen to permeate through the porous graphene are different. The small nanopore (pore-11) can only allow the hydrogen molecules to permeate due to the size restriction. In the systems of bigger nanopores (e.g., pore-13, pore-14, etc.), where the pore size is big enough to allow nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
293
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(302 citation statements)
references
References 33 publications
2
293
1
3
Order By: Relevance
“…Regardless, stabilization of pore size allows for a tighter distribution of pore diameters than that possible in case of a linear growth rate, and also results in subnanometer pores that are predicted to exhibit the selectivity required for nanofiltration, desalination, and gas separation. [1][2][3][4][5] To investigate transport across the created pores, we fabricated a graphene composite membrane (GCM) by direct transfer of graphene from copper foil 36 to a polycarbonate track etch (PCTE) membrane support 24 ( Fig. 5a and Fig.…”
Section: Table Of Contents Graphicmentioning
confidence: 99%
“…Regardless, stabilization of pore size allows for a tighter distribution of pore diameters than that possible in case of a linear growth rate, and also results in subnanometer pores that are predicted to exhibit the selectivity required for nanofiltration, desalination, and gas separation. [1][2][3][4][5] To investigate transport across the created pores, we fabricated a graphene composite membrane (GCM) by direct transfer of graphene from copper foil 36 to a polycarbonate track etch (PCTE) membrane support 24 ( Fig. 5a and Fig.…”
Section: Table Of Contents Graphicmentioning
confidence: 99%
“…Porous graphene 15 is produced as a single sheet of carbon, bonded in a planar, hexagonal structure, with several carbon atoms removed to create a "pore", shown in figure [3] 16,17 which can be used as a nanofilter 18 . Due to graphene's open structure, electrons and protons can freely pass through the lattice with minimal resistance, while restricting the flow of larger molecules, which may only pass through the pores 6 . .…”
Section: Resultsmentioning
confidence: 99%
“…The Hydrogen ions (Protons) are drawn through the membrane of the system toward the cathode, which with the Oxygen molecules, produce water as a waste product. (6) Water is expelled from the system.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…All molecular dynamic simulations were performed in an NVT enable to gases [7]. However, several studies have suggested that graphene has the potential to induce highly selective transport by generation of pore defects [8][9][10][11][12][13][14], in which atoms can be removed from the graphene lattice to create pores of specific size and geometry.…”
Section: Simulation Details and Methodsmentioning
confidence: 99%